Effect of DC voltage on morphology and size distribution of silver nanorods synthesized through plasma-liquid interaction method. (2021) - Shukrullah, Shazia; Naz, Muhammad Yasin; Altaf, Noor ul Huda; Ali, Asghar
Abstract: A plasma-liquid interaction method was used to produce silver nanorods from silver nitrate and sucrose solution at different DC voltages. Sucrose was used as stabilizing and reducing agent in this reduction reaction. A fixed molar ratio of silver nitrate was used to elaborate the effect of DC plasma voltage on shape size and elemental composition of nanorods. The formation of silver nanorods was confirmed from SEM images. Some copper nanoparticles were also formed due to degradation of anode during plasma reduction process, which were uniformly distributed over the surface of nanorods. The nanorods had well-defined shape and alignment at an applied voltage of 4 kV. The elemental analysis provided EDX peaks at 3 keV, 1.8 keV, 0.5 keV and 0.3 keV, which correspond to Ag, Si, O and Cu, respectively. The applied voltage only effected the shape and size of the nanorods. The size of nanorods varied from 662 nm to 964 nm, 483 nm to 703 nm and 572 nm to 841 nm for 2 kV, 4 kV and 6 kV, respectively. The size distribution histograms reveal narrowest size distribution of nanorods at 4 kV voltage followed 6 kV and 2 kV.